STARBUCKS INDONESIA'S BREWING CONTROVERSY : EXPLORING THE CONSUMER BEHAVIOUR AND PRODUCT PERCEPTION IN THE SHADOW OF THE ISRAELI-PALESTINIAN CONFLICT - Gasong, Rosi Aprianti; Sobari, Nurdin (LPPM STIE Muhammadiah Bandung, 2024)
The main objective of this study is to examine how the role and influence of religiosity, consumer animosity and consumer ethnocentrism on the assessment of Starbucks Indonesia products that affect consumer purchasing behavior after the Israeli-Palestinian conflict broke out again in October 2023. Considering Indonesia is the biggest country with Muslim population in the world, how will it react to such a global brand, the biggest coffee corporation in the world and what drives them. The research using quantitative method with validated questionnaires derived from literature is used for data collection. Data were collected from 250 respondents Starbucks Indonesia consumers who are Muslims. This research using the Structural Equation Modeling (SEM) method with a focus on Partial Least Squares (PLS) for framework analysis. The study attempts to add value and give comprehensive details to the existing literature on consumer behavior, especially the role of religiosity, animosity, and ethnocentrism among consumers in Indonesia. The research emphasizes the importance of understanding consumer behavior in diverse cultural contexts and aims to guide brand managers in developing targeted strategies to navigate potential challenges arising from religiously motivated consumer sentiments in the aftermath of the Israeli-Palestinian conflict. The practical implications suggest that brand managers should adopt nuanced marketing strategies in conflict-affected regions, recognizing the diverse consumer sentiments and tailoring campaigns accordingly. Effective communication and CSR initiatives are crucial for maintaining brand loyalty and trust, with a focus on community engagement and interfaith projects. Additionally, ongoing research and feedback mechanisms are essential to monitor and adapt to the changing consumer sentiments in these regions.